Comparative study of yield, intake, chemical composition and nutritive values of gama (<Tripsacum dactyloides</i) oat (Avena sativa) and sorghum (Sorghum bicolor) forages - Islam, MN; Alam, MR; Kabir, AKMA; Das, NG; Khanduker, MM (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to compare the yield, composition and nutrient digestibility of gama (Tripsacum dactyloides), oat (Avena sativa) and sorghum (Sorghum bicolor) forages. Three fodders were cultivated and a metabolism trial was conducted with 3 indigenous sheep in a 3 × 3 Latin Square Design (LSD) for determination of nutrient digestibility. The fresh yield of gama was higher (P<0.05) than that of oat and sorghum. The yield of DM in gama and sorghum was similar and significantly higher (P<0.01) than oat. No significant differences (P>0.05) were observed in DM, OM, CP, NDF and ADF contents among the gama, oat and sorghum forages. The average DM and OM intake in sheep fed sorghum was higher (P<0.05) than that of oat or gama. Sheep fed sorghum or oat showed significantly (P<0.01) higher CP intake than gama. Average NDF and ADF intake was higher (P<0.05) in sheep fed sorghum followed by oat or gama, respectively. The DM digestibility of different forages was found non-significant (P>0.05). The OM digestibility of sorghum was found to be higher (P<0.05) compared to oat or gama. Digestibility of CP was significant (P<0.01) higher sorghum than oat (37 %) or gama (36 %). Higher NDF and ADF digestibility (P<0.05) were found in sorghum and oat, respectively than gama. It was concluded that sorghum (Sorghum bicolor) is better than gama (Tripsacum dactyloides) and oat (Avena sativa) forages. Key words: Gama; Oat; Sorghum; Digestibility DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9678 Bang. J. Anim. Sci. 2010, 39(1&2): 67-74